Peningkatan Keterampilan Bahasa Inggris Kelas 2 Melalui Media Flipchart : Pendekatan Inovatif Di MIS Fathul Jannah - Hesty Widiastuty; Alvin Maulana; Ahmad Julianto; Shifa Soraya Lestari; Muhammad Rafi Zidan; Weni Wulandari; Wilda Cahyani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to improve the English language skills of class 2 students at MIS Fathul Jannah using flipchart media, carrying out interactive learning methods, and evaluating the impact of using flipcharts on student understanding. The results show that using flipcharts effectively improves students' understanding, although it requires time preparation and reliance on teacher explanations. The advantages are material visualization, interaction, and flexibility. Disadvantages include time-consuming preparation, reliance on explanations, and space limitations. In conclusion, using flipcharts can improve students' English skills, but requires careful preparation and training for teachers. Integration with digital learning tools is also needed to increase its effectiveness. Although recommended as an effective learning method for elementary schools, further research is needed to improve the quality of its use.